Ground temperature and permafrost distribution in Hurd Peninsula (Livingston Island, Maritime Antarctic): an assessment using freezing indexes and TTOP modelling - Ferreira, Alice (2020)
The Western Antarctic Peninsula region shows mean annual air temperatures ranging from −4 to −2 °C. Due to its proximity to the climatic threshold of permafrost, and evidence of recent changes in regional air temperatures, this is a crucial area to analyse climate-ground interactions. Freezing indexes and n-factors from contrasting topographic locations in Hurd Peninsula (Livingston Island) are analysed to assess the influence of snow cover on soil's thermal regime. The snow pack duration, thickness and physical properties are key in determining the thermal characteristics and spatial distribution of permafrost. The Temperature at the Top Of the Permafrost (TTOP) model uses freezing and thawing indexes, n-factors and thermal conductivity of the ground, as factors representing ground-atmosphere interactions and provides a framework to understand permafrost conditions and distribution. Eight sites were used to calculate TTOP and evaluate its accuracy. They encompass different geological, morphological and climatic conditions selected to identify site-specific ground thermal regime controls. Data was collected in the freezing seasons of 2007 and 2009 for air, surface and ground temperatures, as well as snow thickness. TTOP model results from sites located between 140 and 275 m a.s.l were very close to observational data, with differences varying from 0.05 to 0.4 °C, which are smaller than instrumental error. TTOP results for 36 m a.s.l confirm that permafrost is absent at low altitude and thermal offsets for rock areas show values between 0.01 and 0.48 °C indicating a small effect of latent heat, as well as of advection.